Factors that Influence Customer Satisfaction and Loyalty of ULaMM At PT. serang Branch Civil National Capital - Hera Afrizal; Agus Salim (DINASTI RESEARCH, 2023)
Micro Capital Service Unit (ULaMM) is a service from PT. Civil National Capital which was established with the intent and purpose of empowering micro and small businesses through financing and management services. This business unit operates in business-intensive locations with the intention of being able to easily provide financing to micro and small entrepreneurs. To be able to maintain and increase customers, companies must strive to create customer satisfaction and so that customer loyalty can also be created. This study aims to examine the effect of service quality, ULaMM Regular product quality on customer loyalty through customer satisfaction at PT. Serang Branch Civilian National Capital. This study uses a quantitative approach with Structural Equation Modeling (SEM) using the PLS program. The Sobel test was conducted to determine the effect of mediation or intervention. The unit of analysis used is all ULaMM regular customers of PT. Serang Branch Madani National Capital which has top up at least twice. The sample consists of 63 respondents (saturated sample). Data collection techniques were carried out using a questionnaire. It is hoped that the results of this study can prove that service quality and product quality have a positive and significant effect on customer satisfaction and loyalty.